Factors Affecting the Students’ Satisfaction on Learning and Teaching Process with Perspective as a Consumer of University - Luky Susilowati; Pandji Sugiono (Nusantara Science and Technology Proceedings)
Competition in college also intensify the growing number of university, courses and programs offered, this situation demands every university creates a competitive advantage to compete in the market with the private university, State University and foreign universities, especially from Malaysia and Singapore. What competitive advantage possessed by a university needs to be understood so they can build a strategy for improving the quality and simultaneously improve quality. This study was conducted to analyze multiple factors that affect student satisfaction in teaching and learning in the UPN Veteran of East Java. The samples in this research are the students of UPN Veteran of East Java who are still active. The sampling technique used in this study is a probability sampling technique with proportional stratified random sampling method, data analysis was conducted using the method of SEM-based components by using Partial Least Square (PLS) selected as an analytical. The finding of the research shows that, Facilities, Administration Staff, Academic Staff and Academic Processes able to contribute to improve the satisfaction of students in the learning process.